Code Mixing Usage in Imperfect: Karier, Cinta & Timbangan Movie Directed By Ernest Prakarsa - Wibowo, Ary Iswanto; Ramdhani, Zulfi; Rahayuningsih, Retno (Journal of Pragmatics Research, 2022)
The objective of this study was to analyze the types, factors, and functions of code-mixing in the movie Imperfect: Karier, Cinta Timbangan directed by Ernest Prakasa. The study uses the descriptive qualitative method. The subject data is taken from the utterances of dialogue on each person in the movie and the object data is taken from the main characters. As a novelty, the study shows theoretical contribution by exploring types, factors, and the function of code-mixing in the movie. This type is determined by the mixing between inter sentential and Intra lexical mixing. This has not been studied in previous research. While the other research studies common types of code-mixing, they ware insertion, alternation, and congruent lexicalization. So, why the authors need to obtain this research because they contribute to adding a new understanding in code-mixing. The result of this study showed that the most widely used type of code-mixing was inter-sentential mixing. The most widely used code-mixing factors are domicile and conversation time. Meanwhile, the most widely used code-mixing function is repetition. The implications of this research are in the form of the preparation of a Learning Implementation Plan (RPP). Inter sentential, intra-lexical, code-mixing research in the film Imperfect: Career, Love Scales directed by Ernest Prakasa will be implied in English courses. Implications will be carried out at the Bina Sarana Informatika university level in English drama courses about analyzing the content and language of the plays read or watched. This is done by demonstrating a drama and paying attention to the content and language. Keywords: inter-sentential, intra-lexical, code-mixing.